Problematising separated children:a policy analysis of the UK ‘Safeguarding Strategy: Unaccompanied asylum seeking and refugee children’ - Dikaiou, M. (2021)
While international and national policies, strategies and legislation have been designed to address the problems of forced displacement, they also form a vital role in the discursive construction, governance and regulation of those who have been displaced. This paper critically interrogates the ‘UK Safeguarding Strategy: Unaccompanied Asylum Seeking and Refugee Children’ to highlight the ways in which unaccompanied asylum seeking children (UASC) are implicitly constructed as a policy problem. Drawing on Foucault, and using a novel analytic method (WPR) for studying problematisation within policy, this paper moves beyond the policy definition of an unaccompanied asylum seeking child to unearth characterisations that the policy ascribes to this group of children, and in particular the conceptual boundaries established for the way society thinks about UASC. These conceptual boundaries are divisive in nature, including suspicion around routes of arrival to the UK; constructions of risk; and questions about the responsibility of providing care and of being in need of care. The significance of the paper lies in its aim to use the examination of the discursive practices of the UK’s Safeguarding Strategy as a starting point to open a broader discussion around how UASC are constructed and governed, nationally and internationally